The narcissistic leadership style perspective in terms of factors, roles and influences in the organization - Suhardoyo Suhardoyo (STABN RADEN WIJAYA WONOGIRI, 2022)
Abstrak Para pemimpin narsistik atau narsisme kepemimpinan memiliki sistem kepercayaan dan gaya kepemimpinan yang luar biasa, dan apa adanya serta dimotivasi oleh kebutuhan mereka akan kekuasaan dan kekaguman daripada perhatian empati terhadap konstituen dan lembaga mereka memimpin. Kami meninjau dan menilai literatur teoritis dan penelitian tentang narsisme pemimpin untuk memahami potensi positif dan konsekuensi negatif dari kepemimpinan narsissistik dengan gaya kepemimpinan yang ada dan dalam hubungan narsisstik kepemimpinan untuk dijadikan model kepemimpinan. Dalam konteks ini, kami memberi definisi narsisistik kepemimpinan dan meringkas penyebab kepemimpinan narsistik. Kemudian, memperkenalkan tentang pengaruh positif dan negatif dari kepemimpinan narsistik serta pengaruhnya dalam tranformasi organisasi. Narsistik merupakan ciri kepribadian yang dianggap bertanggung jawab untuk hasil perilaku positif dan negatif yang memengaruhi keputusan dan tindakan. Kepengaruhannya akan sangat dipengaruhi oleh kedominannya pengaruh perilaku tersebut dalam diri pemimpin. Makalah ini merevieu hubungan narsisistik kepemimpinan dalam organisasi faktor, peran dan dampaknya pada organisasi dalam tranformasi organisasi Kata kunci: Narsisme , Kepemimpinan, organisasi Abstract Narcissistic personality traits that include grandeur, arrogance, self-absorption, rights, fragile self-esteem, and hostility are attributes of many powerful leaders. Narcissistic leaders have an extraordinary system of belief and leadership style, and what they aregenerally motivated by their need for power and admiration rather than empathetic attention to their constituents and lead institutions. However, narcissists also have a great charisma and vision that is essential for effective leadership. We review and critically assess the theoretical literature and research on narcissistic leaders to understand the potential positive and negative consequences of their leadership, their leadership trajectory, and narcissistic relationships for established leadership models. In this context, we define narcissism and narcissistic leadership and summarize the causes of narcissistic leadership. Then, by definition, we introduce the positive and negative effects of the narcissistic leadership and its influence in organizational transformation. Narcissism is a personality trait that is perceived to be responsible for positive and negative behavioral outcomes that affect decisions and actions. His influence will be influenced by the dominance of such behavior in the leader. This paper explores the relationship of narcissism with leadership in the organizational context and presents its impact on the organization in achieving organizational transformation Keywords: Narcissistic, Leadership, Organization